Modelagem e simulação para avaliação de desempenho de sistema fotovoltaico do tipo SIGFI-45 operando com diferentes configurações - BULHOSA, Lucas dos Santos (Universidade Federal do Pará, 2024)
The present work aims to evaluate the performance of a photovoltaic system of type “Sistema Individual de Geração de Energia Elétrica com Fonte Intermitente – SIGFI”, using different equipment configurations, such as photovoltaic generator and charge controller, bymodeling the system components and simulating them using Matlab/Simulink software. For validation of the developed model, monitored data was used from a real SIGFI system with a minimum monthly energy availability of 45 kWh, implanted in the external area of the “Grupo de Estudos e Desenvolvimento de Alternativas Energéticas da Universidade Federal do Pará (GEDAE/UFPA), whose electrical parameters were monitored on the dc and ac side of the system, as well as environmental parameters. Practical tests were thus carried out with different equipment configurations and the data obtained in these tests were also used to validate the results of the simulations of the model developed for the system. It should be noted the tests were designed using charge controllers with and without the Maximum Power Point Tracking (MPPT) mechanism, as well as direct coupling of the photovoltaic generator to the battery bank (self-regulated operation). After validating the model, it is possible to use the platform to simulate the operational performance of the system for different irradiance and temperature profiles using the equipment configurations considered, and also operating with different load curves and different initial state of charging of the battery bank. Among the various simulations carried out, the best results were obtained for the case with a MPPT mechanism, modules with 60 cells and when consumption peaks are close to the photovoltaic production peak, reaching results where 58% of the load was supplied directly by the photovoltaic generation